Temporal 3D graphical data management from a database perspective - Chau, Vo Thi Ngoc; Chittayasothorn, Suphamit (My University, 2009)
According to recent advances in computer science and engineering, three dimensional (3D) graphical data is of growing interest in many application areas. In this paper, a data management technique is proposed to handle 3D graphical data with the time dimension from a database perspective. Different from the existing works, our technique deals with 3D graphical data in all of the three various aspects: the visual aspect for the 3D graphical data part, the semantic aspect for the metadata part, and especially the temporal aspect for changes over the time. As a result, 3D graphical data can be managed properly with semantics and time. Therefore, many front-end applications can conveniently have access to them at both graphical and semantic data levels for sharability and reusability. © 2009 IEEE.
Keywords: 3D graphical object; Conceptual schema; Metadata; Object relational data model; Temporal database